Coupling of computation simulation and hands-on experience in process control laboratory inline with IR 4.0 oriented education - Serene Lock, Sow Mun; Irene Lock, Sow Mei; Lim, Lam Ghai (Universiti Teknologi MARA, Kedah, 2023)
Integrating principles of Industry 4.0 into hands-on laboratory programs is crucial for mastering process control. However, many laboratories curriculum mainly rely on direct instrument use. This does not adequately train students for the demands of Industry 4.0. In response, Universiti Teknologi PETRONAS introduces an updated curriculum, transitioning to simulation-driven laboratories. The transition is especially valuable in CEB3032 Chemical Engineering Laboratory III for Jan and May 2021 cohort that involves 207 and 162 students to address the challenges in developing genuine psychomotor abilities by simply viewing video recordings since they are not interacting with the actual devices during the COVID-19 pandemic. Before rolling it out, the university meticulously chooses experiment suitable for process simulation. These are then modeled using a dynamic simulation tool applying ordinary differential numerical techniques, e.g., Euler's, Runge Kutta and Gear, for lumped parameter systems and partial differential methodologies, such as finite difference, for distributed parameter systems, respectively. As part of this curriculum, students create simulations, perform experiments, document results, and juxtapose their findings with traditional laboratories presented to them. The application of advanced Bloom's Taxonomy and the Five Es Inquiry-Based Learning is evident, as students actively engage in establishing and designing their own laboratories, starting with the foundational control systems. Feedback and student performance metrics serve as indicators of this approach's success. After adopting the IR 4.0-focused curriculum, there is a noticeable enhancement in students' results, evidenced by an increase in top grades such as A's and a higher median score. The learning outcomes have also seen a boost, with roughly 30% more students achieving grades ranging from B to A. Majority of the students find that integrating process simulation into CEB3032 has aided in applying their knowledge in the process control laboratories too. The success underscores this methodology’s viability for broader academic adoption.